Identification and DNA Profiling of superior grain quality genotypes in rice (Oryza sativa L.) - D. PADMAJA; S. LAXMAN, S. THIPPESWAMY, Y. CHANDRAMOHAN, B. MADH B. MADHAVILATHA, K. PRAVALIKA (The Journal of Research, PJTSAU, 2017)
Rice (Oryza sativa L.) is the only cereal crop cooked and consumed mainly as whole grains and quality considerations are much more important than any other food crop, which define market and end-use qualities. Grain quality parameters of twenty five rice genotypes (9 Jagtial varieties, 6 pre-released cultures, three mega varieties, one Nellore variety, one private company variety and five hybrid rice parental lines) were estimated at RRS, RARS, Jagtial during Kharif 2013, to identify the genotypes having better quality characters. It is revealed that hulling percentage is very good in all the genotypes and ranged from 78% (Swarna) to 84% (JGL11470).The milling recovery varied from 64% JGL11118) to 72% (JGL23710).The Head Rice Recovery varied from 50% (JGL23714) to 62% (JGL3855).The kernel length is highest in MTU1010 (6.7mm) and lowest is 5mm (JGL23710). 13 varieties had short slender type(SS), 3 were of medium slender(MS) and 9 were of long slender(LS) grain type. Amylose content was intermediate in most of the tested genotypes except in CMS46B (10%) and highest was in Swarna (26.6%). Varieties with intermediate amylose are fluffy and retain soft texture on cooling, so the intermediate ones are mostly preferred for cooking. One SSR marker (RM444) out of ten was able to differentiate JGL1798, JGL19621 and MTU1010 from other genotypes. Among the quality traits, 1000 grain weigh, Amylose% and alkali spreading value recorded highest GCV and PCV followed by Kernel length and breadth. Milling % and amylose % showed significant positive correlation with HRR and L/B ratio showed significant negative correlation. Hence, selection for improvement based on these parameters will be a right step in right direction.